Constructing Clean Living Behavior through Local Culture: Evidence from Penglipuran Traditional Village, Bali - Muhammad Ilyas; Syamasu A Kamaruddin; Ahmadin; Arlin Adam (Journal of Indonesian Scholars for Social Research, 2026)
Clean living behavior is often understood as an outcome of individual awareness or public health intervention. However, in culturally rooted communities, such behavior may also be shaped by collective values, customary rules, and everyday social practices. This study examines how local culture constructs and sustains clean living behavior in Penglipuran Traditional Village, Bali, a village widely recognized for its clean and orderly environment. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving traditional leaders, village stakeholders, and community members. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with source and method triangulation used to strengthen validity. The findings show that clean living behavior in Penglipuran is constructed through the internalization of cultural values, the enforcement of customary rules known as awig-awig, collective participation through gotong royong, and informal social control. Cleanliness is not merely practiced as an individual habit, but is understood as a form of social responsibility, cultural identity, and harmony between humans and their environment. This study highlights the importance of local wisdom as a socio-cultural foundation for sustainable environmental behavior and community-based cleanliness governance.